Quality of white Gurgutuba creole beans stored in silo bags and PET bottles - Magalhaes, Valter Barbosa; de Sousa, Adalberto Hipólito (Revista Agrogeoambiental, 2020)
Hermetic storage in silo bag has provided a viable alternative for farms. This study evaluates the use of silo bags as an alternative for storing creole beans. The experiment was conducted in the UFAC seed laboratory. The beans were stored in silo bags for 30, 60, 90 and 120 days or in PET bottles, which is the common practice. In the control treatment, PET bottles sealed with organza fabric were used. The experimental model was factorial CRD with subdivided plots and four replications, with the plots being storage conditions; and sub-plots, storage periods. The degree of infestation, moisture content, apparent specific mass, germination percentage and electrical conductivity were evaluated at 30 - day intervals. There was significant variation (p < 0.05) between storage types Zabrotes subfasciatus (Boheman) and Acanthoscelides obtectus (Say) (Coleoptera: Chrysomelidae, Bruchinae), then infestations occurred. Infestation using these bruchids was < 7% in the beans stored in the silo bag and PET bottle. For the control treatment, the degree of infestation was slightly higher (p < 0.05) with rates of > 90% after 120 days. The moisture content, specific mass, germination, and electrical conductivity of the beans stored in the silo bag and PET bottle preserved the characteristics analyzed over the 120-day period with the exception of control treatment. Storage in silo bags is an effective alternative for controlling infestation and maintaining quality, in terms of moisture content, specific mass, germination, and electrical conductivity, for up to 120 days.